Testing the behavior of GlobalFiler® PCR amplification kit with degraded and/or inhibited biological samples. (December 2015) - Bogas, V.; Carvalho, M.; Corte-Real, F.; Porto, M.J.
Abstract: The achievement of complete genetic profiles of degraded and/or inhibited biological samples is a challenging task for forensic scientists. Our aim was to find out the behavior of GlobalFiler ® PCR amplification kit in the presence of difficult samples and its ability to substitute or to be complemented by AmpFℓSTR ® MiniFiler™ kit. Degraded bloodstains were extracted by three methods, quantified and amplified with AmpFℓSTR ® IdentiFiler™, AmpFℓSTR ® MiniFiler™ and/or GlobalFiler ® PCR. In 6 of the 14 analyzed samples, GlobalFiler ® kit enabled a complete genetic profile even when the sample had a DNA concentration as low as 0.0049 ng/ml, while in some of these samples Minifiler™ provided a partial profile or didn't amplify any of the markers in study.